A dendritic cell receptor-targeted chimeric immunotherapeutic protein (C-HBV) for the treatment of chronic hepatitis B - Allan Ma; Bruce Motyka; Klaus Gutfreund; Yuenian Eric Shi; Rajan George (Taylor & Francis Group, 2020)
In chronic Hepatitis B Virus (HBV) infections HBV-specific T cells are functionally impaired. Immunotherapy may restore HBV-specific T cell responses essential for sustained disease remission off-treatment and induction of a functional cure. Chimigen® Molecules are fusion proteins of antigen(s) with the Fc fragment of a xenotypic antibody designed to target specific receptors on dendritic cells (DCs). Here we describe the production and pre-clinical evaluation of Chimigen® HBV (C-HBV), containing HBV PreS1 and PreS2 peptide fragments, HBV core and murine Fc, produced in insect cells. C-HBV binding to immature DCs and internalization by endocytosis was FcγRII (CD32) and mannose receptor (CD206) dependent and led to increased MHC I and MHC II surface expression. Upon exposure of human T cells isolated from HBV un-infected healthy and chronically HBV-infected donors to C-HBV-pulsed mature DCs ex vivo, C-HBV induced vigorous T cell proliferation and enhanced expression of IFN-γ, TNF-α, perforin and granzyme B in both CD4+ and CD8+ T cell subsets. Re-stimulation of C-HBV-activated T cells from chronically infected donors with HBV PreS1/PreS2 and core overlapping peptides induced IFN-γ production in both CD4+ and CD8+ populations. C-HBV-activation of peripheral blood mononuclear cells (PBMCs) from chronically HBV-infected patients stimulated granzyme B production by CD4+CD25− T responder (Tresp) cells, accompanied by an increase in Annexin V staining on CD4+CD25+ T regulatory (Treg) cell phenotype, consistent with apoptosis. The observed HBV-specific cellular responses induced by C-HBV ex vivo suggest that C-HBV is a promising immunotherapeutic candidate for the treatment of chronic HBV infections.